Understanding a pedagogy of teacher education : contexts for teaching and learning about your educational practice - Butler, Brandon M.; Bullock, Shawn Michael, 1976- (New York, NY : Routledge, 2024)
"Providing readers with insights and examples of how teacher educators learn and teach a pedagogy of teacher education (PTE), Butler and Bullock organize a wholistic and practical resource for the next generation of teacher educators. Expanding on the highly referenced scholarship of John Loughran and Tom Russell, "Understanding a Pedagogy of Teacher Education" explores the learning of PTE through individual and collaborative endeavors, and large-scale institutional and cross-national initiatives. Contributors highlight their experiences teaching PTE in formal learning spaces, in international workshop settings, and on the program-wide scale in order to uncover how they came to understand PTE and enact it effectively. Each chapter connects broad strokes concepts of PTE to well-defined teacher education fields, such as social justice, literacy, early childhood education, and communities of practice. Blending well- established theory with contemporary examples, this book is a great tool for teacher education faculty, doctoral students, and those interested in improving their PTE or supporting others in their PTE learning"--
Understanding a pedagogy of teacher education / Brandon M. Butler and Shawn Michael Bullock -- Constructing a personal pedagogy of teacher education / Tom Russell -- New positions, new pedagogies : learning and becoming in a novice teacher educator community of practice / Olivia Williams, Colleen Gannon, South Holden, and Jennifer Burris -- Learning a new pedagogy of teacher education through critical friendship : examining mindfulness as content and as pedagogy / Megan Madigan Peercy and Shawn Michael Bullock -- Preparing all teacher educators? : considerations for the specialized work of teacher education in a pedagogy of teacher education course / Alexander Cuenca, Chelsea Brinda, Ryan Cowden, and Mariah Pol -- Unpacking practice : teaching, while learning, a pedagogy of teacher education / Brandon M. Butler -- Aligning pedagogies of teacher education with the teaching of social justice / Dylan Scanlon, Elaine Murtagh, Antonio Calderón, Ann MacPhail, and Claire Walsh -- Navigating crisis while learning a justice-oriented pedagogy of teacher education / Elizabeth Ann Tetu -- Exploring the complexity of embedding social justice into a pedagogy of literacy teacher education / Pooja Dharamshi, Lydia Menna, and Clare Kosnik -- The persistent relational disconnect of teacher education : reimagining teacher education pedagogy as feminists / Monica Taylor and Emily J. Klein -- A sociocultural perspective to learning a clinical pedagogy in and of teacher education / Megan E. Lynch and Rebecca West Burns -- A collaborative faculty approach to a practice-based pedagogy of teacher education / Carla Finkelstein, Lijun Jin, Maria Perpetua Liwang, Pamela S. Lottero-Perdue, Vicki McQuitty, Shannon Monacelli, Stephanie Moody, and Laurie Mullen -- A pedagogy of teacher educator development : lessons learned and future considerations / Eline Vanassche, Paulien Meijer, Helma Oolbekkink-Marchand, and Ruben Vanderlinde -- Signaling new directions : lessons for understanding a pedagogy of teacher education / Shawn Michael Bullock and Brandon M. Butler.
Keywords: Teachers -- Training of; Education -- Study and teaching (Higher); Critical pedagogy; EDUCATION / General; EDUCATION / Higher; EDUCATION / Professional Development